2020
DOI: 10.3389/fenrg.2020.545431
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Cu/ZnO-Based Catalysts for Carbon Dioxide Hydrogenation to Methanol, and the Use of Methanol As a Renewable Energy Storage Media

Abstract: Heterogeneous catalytic hydrogenation of carbon dioxide (CO2) to methanol is a practical approach to mitigating its greenhouse effect in the environment while generating good economic profits. Though applicable on the industrial scale through the syngas route, the catalyst of Cu/ZnO/Al2O3 suffers from a series of technical problems when converting CO2 to methanol directly, which include low single-pass conversion, low methanol selectivity, requiring high pressure and fast deactivation by the reverse water gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 214 publications
(324 reference statements)
2
38
0
Order By: Relevance
“…13 The catalyst activity is still under investigation, and recent publications demonstrate that there exists the potential for improving the catalyst formulation also in the perspective of CO 2 hydrogenation to methanol. 14,15 Deepening the analysis of new technologies and apparatus (Figure 5), it is worth noting that most of the innovations in the last three decades deal with feedstock. This is mainly due to the change of raw materials used in syngas production, first from fossil to renewable sources and, then, to CO 2 for direct conversion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 The catalyst activity is still under investigation, and recent publications demonstrate that there exists the potential for improving the catalyst formulation also in the perspective of CO 2 hydrogenation to methanol. 14,15 Deepening the analysis of new technologies and apparatus (Figure 5), it is worth noting that most of the innovations in the last three decades deal with feedstock. This is mainly due to the change of raw materials used in syngas production, first from fossil to renewable sources and, then, to CO 2 for direct conversion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yu et al [96] demonstrated through spin-polarized DFT calculations that adsorption and dissociation of CO 2 was dependent on the Co particle size. They showed that Co 55 nanoclusters had the highest CO 2 dissociation activity in comparison to Cu-based materials have gained much attention in the CO 2 conversion process due to their wide applicability in the different conversion processes and low cost [12,97]. Despite these and other massive studies, the activation of CO 2 on Cu catalysts is still an issue due to the poor understanding of its mechanism.…”
Section: Co 2 Activation On Representative Pure Metalsmentioning
confidence: 99%
“…Different types of catalysts have been investigated for the thermocatalytic hydrogenation of CO 2 to methanol, including supported metal [ 8 , 9 ] and metal oxide [ 10 , 11 ] catalysts. Cu-based catalysts have been reported to have the best activity for methanol production under industrially relevant conditions (5–10 MPa and 200–300 °C) [ 12 , 13 ]. The Cu-ZnO-Al 2 O 3 catalyst prepared via the co-precipitation method is the industrial catalyst used for methanol production from CO + H 2 ; thus, the Cu-ZnO-based catalysts are widely investigated for CO 2 hydrogenation to methanol as well [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%